Study on Steam Excitation Forces Induced by Tip Seal Leakage Flow in Steam Turbines - Pan Li; Huan Wang; Haichao Peng; Heyong Si; Tieliu Jiang (Machines, 2025)
This study aims to elucidate the mechanisms by which tip seal leakage flow induces steam excitation, thereby enhancing the operational safety of steam turbines. Using numerical simulations, it investigates the detailed characteristics of the flow field in the turbine tip seal cavity. By introducing Boundary Vorticity Flux (BVF) into the tip seal flow field, this research explores the relationship between leakage vortex structures in non-uniform flow fields at the blade tip and the resulting steam excitation forces. The results demonstrate that, during eccentric rotor operation, the extent and intensity of vortices within the seal cavity vary, lead to changes in the BVF distribution along the shroud surface, which in turn alter the tangential forces and induce variations in lateral excitation force at the blade tip. Additionally, the non-uniform flow in the tip seal clearance induces circumferential pressure variations across the shroud, leading to adjustments in radial excitation force at the blade tip.